Klastering Kecepatan Internet Operator Telkomsel Berdasarkan Sebaran Site BTS (Base Transceiver Station) Menggunakan Metode DBSCAN - Alifudin, Arif; Pratama, Irfan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The development of cellular telecommunications technology has now reached a more advanced stage with the presence of 4G LTE technology. Compared to previous technologies such as 3G and 2G, this technology offers data transfer capabilities with much better access speeds. This makes 4G LTE the backbone for modern communication services that support users' needs for fast and stable internet access. However, even though 4G LTE technology has been widely implemented, there are still challenges that need to be overcome to ensure network quality remains optimal. The quality of the internet network in the Special Region of Yogyakarta (DIY) has experienced significant improvements in recent years, but obstacles such as limited infrastructure are still felt, especially in rural and outermost areas. This research aims to analyze and group areas based on network quality. Therefore, data mining analysis of existing data is needed using the DBSCAN algorithm so that clusters will be formed which are divided according to network quality. After carrying out analysis using the epsilon value = 0.5 and the minpts value = 5, the clusters formed were 5 clusters with a silhouette value of 0.216471397367446, which indicates that the quality of the clustering is relatively low, which is possibly caused by less than optimal distribution of data or parameters. Nevertheless, the clustering results obtained still provide useful insights for analyzing site distribution and network performance.